Urea‐based recirculation validation of the symmetrical palindrome catheter. Issue 4 (16th August 2017) - Jonczyk, Martin; Althoff, Christian; Slowinski, Torsten; Lieker, Ina; Naik, Marcel; Auer, Jonas; Marcos, Raúl García; Duka, Ejona; Hamm, Bernd; de Bucourt, Maximilian
SUMMARY: Background: High blood flow and low recirculation rates are central for adequate haemodialysis. A new symmetrical tip has been invented promising efficient haemodialysis even if the ports are reversed. Objective: To evaluate access recirculation of the 'palindrome' catheter and to report initial experiences in a clinical setting. Material and methods: After implantation of the new catheter in 20 patients (male: 14; female: 6; mean age 72 ± 12.2), access recirculation was evaluated using the urea‐based recirculation test. After 30 minutes of haemodialysis, ultrafiltration was stopped and arterial and venous samples were taken. Afterwards, the blood flow rate was reduced to 120 ml/min. Another systemic arterial blood sample was taken 10 seconds after the blood pump was switched off. Results: All 20 interventions were performed successfully without complications. The average recirculation rate was 8.1% with a median of 2.5% ranging from 0 to 85.8%. Recirculation rates under 5% were measured in 13 patients and more than 10% recirculation were found in two patients. The median of days between catheter implantation and recirculation assessment was the day following implantation. Conclusion: The new symmetrical catheter presented low recirculation rates in a clinical setting. Since there is just a single tip, fluoroscopic placement in the right atrium is facilitated.